Monocyte at diagnosis as a prognosis biomarker in tuberculosis patients with anemia - Luo, Mengxing; Zou, Xin; Zeng, Qibing; Wu, Yaxing; Yang, Hua; Qin, Lianhua; Zheng, Ruijuan; Yu, Fangyou; Hu, Yang; Liu, Zhonghua (Frontiers in Medicine, 2023)
Background Anemia leads to a lower cure rate and poor prognosis in tuberculosis patients. Effective predictors for the prognosis of tuberculosis with anemia (A-TB) are urgently needed. Monocyte has been proven to be a prognostic biomarker of many lung diseases. Whether monocyte that the predominant innate immune cell as early defense against tuberculosis can predict A-TB is not known. Methods Data for A-TB patients with initial treatment in Shanghai Pulmonary Hospital were retrospectively collected and analyzed. Logistics regression analysis was used to study the correlation between peripheral blood cells and treatment outcomes. The receiver operating characteristic (ROC) curve was used to determine the cut-off value. We estimated a 12-month prognosis using Kaplan–Meier techniques. The Cox proportional hazards model was used for the univariate and multivariate analyses to analyze the predictors of poor prognosis of A-TB. Results Of 181 patients analyzed, 94 were cured and 87 non-cured. Logistic regression analysis identified monocyte as an independent immune-related risk factor for the prognosis of A-TB (OR: 7.881, 95% CI: 1.675–37.075, P = 0.009). The ROC curve analysis proved that the most discriminative cut-off value of monocyte was 0.535 × 10^9/L. K–M analysis demonstrated that the cumulative cure rates of A-TB were significantly higher in A-TB with monocyte < 0.535 × 10^9/L (69.62%) than that in those with monocyte ≥ 0.535 × 10^9/L (38.24%) (Log-rank, χ2 = 16.530, P < 0.0001). On univariate and multivariable analysis, monocyte was an independent predictor of poor prognosis in A-TB. Similarly, monocyte was also an independent predictor of poor pulmonary cavity closure in A-TB (HR: 3.614, 95% CI: 1.335–9.787, P = 0.011). Conclusion In A-TB patients, elevated monocyte was associated with poor prognosis and poor cavity pulmonary closure. Monocyte may provide a simple and inexpensive prognostic biomarker in A-TB.